A Review of In-House Corrosion Testing Methodology for Metallic Stents: Enhancing Durability and Performance - Dr. Kothwala Deveshkumar Mahendralal; Bhatt Chirag; Patel Chirag Jitubhai (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Background: Metallic implantable stents are essential in cardiovascular and peripheral vascular interventions. Their safety and functional longevity are critically dependent on corrosion resistance, given their continuous exposure to harsh physiological environments. Traditional corrosion testing methods, often outsourced, lead to increased operational costs and longer development cycles. Objective: This article presents the development and validation of an in-house corrosion testing methodology for metallic stents, aligned with ASTM F2129 standards, and assesses its effectiveness in simulating physiological conditions and producing reproducible results. Methods: The corrosion assessment protocol consists of sample immersion in saline solution, subsequent heating in boiling water, followed by cooling at body temperature for 48 hours. The samples are then dried and examined under an optical microscope to detect corrosion. Results: The in-house method showed high reliability and consistency with external lab data, significantly reducing lead times and improving quality assurance integration. Microscopical analysis revealed progressive degradation patterns, validating the method’s effectiveness in mimicking in vivo conditions. Conclusion: This validated corrosion testing methodology provides a cost-effective, scalable solution for routine assessment of metallic stents. It enhances control over testing parameters and ensures regulatory compliance. Further optimization will target advanced materials and emerging stent designs to sustain industry relevance.